Pars Intermedia Pituitary Dysfunction Syndrome in Mare of the Creole Race - Coelho, Ana Carolina Barreto; Fröhlich Lauxen, Lucas; Moreira da Rosa Silva, Lucas; Anastácio, Edenara; Brasil Dutra Lima, Natalia; Alberto Machado, Guilherme; Simone Viégas Sallis, Eliza; Lopes Simão, Beatriz (Acta Scientiae Veterinariae, 2024)
Background: Pituitary dysfunction in the pars intermedia is a neuroendocrine disease that affects elderly horses. We observed clinical signs, such as hirsutism, laminitis, weight loss, polyuria, and polydipsia. Basal hypercortisolinemia, hyperglycemia, neutrophilia and elevated liver enzymes were revealed in the laboratory test. However, in cases similar to the one presented herein, a post mortem examination of the pituitary gland can confirm the diagnosis through macroscopic and histological examination. The primary aim of the present work is to report a case of pars intermedia pituitary dysfunction in a creole mare. Case: A 14-year-old creole horse was brought to the Nova Santa Rita-RS clinic with clinical suspicion of colic syndrome. For 20 days, the clinical manifestations were ataxia, wide-based walking, and progressive weight loss. Physical examination revealed cranial nerve changes, respiratory noise, and apathy. Leukocytosis and increased glycemic index were noted during the hematological examination. The animal was euthanized and sent for necroscopic examination after the clinical condition deteriorated over the next 4 days. Visual examination of the cadaver revealed moderate hirsutism. The pituitary gland was enlarged and emerged from the pituitary fossa when the brain was removed, but it maintained its structure. Other signs of a Strongylus infection included pulmonary edema, hepatomegaly, and parasitosis. Histologically, the lung showed pyogranulomatous pneumonia. The liver had fatty degeneration of hepatocytes and the intestinal mucosa had lesions compatible with Strongylus enteritis. In the hypophysis there was congestion and marked proliferation of polyhedral to fusiform cells arranged in cords separated by connective tissue septa, invading and compressing the pars nervosa in the pars intermedia. The cell borders were indistinct, the cytoplasm was slightly biophilic and granular, and there was an evident nucleolus, indicating a pituitary adenoma causing pars intermedia pituitary dysfunction as well as pyogranulomatous pneumonia. Discussion: This condition occurs due to the loss of dopaminergic regulation of the pars intermedia, resulting in high pro-opiomelanocortin (POMP) and cortisol cleavage products production. Diagnosis of pars intermedia pituitary dysfunction is often difficult, but it was possible to reach a conclusion by combining clinical history, animal profile, and macroscopic and histological lesions. Clinical manifestations, such as apathy, ataxia, wide-based locomotion, cranial nerve alteration, and walking in circles are explained by an increase in the pituitary gland, which compresses adjacent tissues. The catabolic effect of increased cortisol in the body causes progressive weight loss, muscle mass loss, leukocytosis, increased glycemic indexes, and changes in liver enzymes. Excess cortisol in the body also has an immunosuppressive effect, which explains why the animal had secondary conditions such as pyogranulomatous pneumonia and parasitic enteritis. However, stressors such as handling and transport can also be considered as facilitators for the condition. Even in winter, subtle clinical signs, such as increased coat thickness, should be considered by the veterinarian. Despite their importance in equine medicine, cases of adenoma causing pars intermedia pituitary dysfunction are uncommon. Because the clinical signs are not very specific and can be confused with other diseases, necropsy and histopathology were critical for the diagnosis. Keywords: adenoma, neuroendocrine disease, equine, pituitary. Título: Disfunção pituitária da pars intermedia em égua da raça Crioula Descritores: adenoma, doença neuroendócrina, equino, hipófise.